Ensino de Geografia e Literatura: crítica, fundamentação metodológica e mediação pedagógica a partir da obra de Eduardo Galeano - Souza, Alex Cristiano de (2021)
This work analyzes the relation between geography teaching and literature, searching for didactic and theoretical-methodological foundations that orient the pedagogical mediation through the literary work in the geography teaching in basic education (primary and secondary education), taking the historical-critical pedagogy and historical-cultural psychology as references and pedagogical ground. To this end, this research aims at the following objectives: to analyze studies involving geography teaching and literature carried out at the postgraduate level in Brazil, identifying and discussing aspects of its theoretical and methodological conceptions; to comprehend imagination and creativity as a historical-cultural process and its contributions to school education; to identify the grounds of the historical-critic didactics for the use of literature in the mediation of geographical knowledge in basic education and; from those groundwork, to demonstrate the relation between literature and science through the dialogue between the work of Eduardo Galeano and geography. Therefore, we address the logical course of teaching and the logical course of learning as a unity of the educational work in the production of the student’s knowledge, in articulation with the proposal of reading the geographical space that runs from the visible to the invisible and vice versa. We also explore the creative activity as an element of the didactic groundwork, in the actualization and contextualization of the work by the students. With the foundations we arrived at, we undertook an analysis of the literary work of Eduardo Galeano for the geography teaching, focusing on globalization as curricular content of the school subject, employing methodological procedures to articulate fundamentals of Geography’s, Education’s and literature’s approach, and to place author, work, reader and geographical knowledge in dialogue, moving between problematization, instrumentalization and catharsis, enabling new analysis and relations in the social practice. From the research carried out and its results, we can affirm that the studies and approaches of Geography, Education and Literature based on dialectical historical materialism provides didactic, theoretical and methodological foundations consistent and coherent to geography teaching through literary works that make possible the sublation of subjectivists, inconsistent or eclectic approaches, predominant in the academic studies involving literature and geography teaching.